Adductor Canal Block (ACB) as an Adequate Analgesia Post Anterior Cruciate Ligament Repair - Utama, Sigit Prasetya; Kuntoadi, Danang; Yuliana, Friskha (JAI (Jurnal Anestesiologi Indonesia), 2024)
Background: Anterior cruriate ligament (ACL) injury is one of the most common cases in knee injury. Inadequate pain management will cause a decrease in quality of life, daily living abilities, increase hospitalization costs, and progressively causing chronic pain. Selection of inappropriate peripheral nerve block (PNB) can reduce range of movement ROM. Abductor canal block (ACB) is expected to facilitate adequate analgetic, improve early mobilization and ambulation, reduce the risk of post operative nausea vomiting (PONV), and needs for other analgeticsCase: A 21-year-old male patient with a diagnosis of ACL rupture knee (S) who will be performed anterior cruriate ligament recontruction (ACLR) procedure with physical status ASA II, premedication ondancentron 4 mg and dexamethasone 5 mg intravenously. Regional anesthesia subarachnoid block, at L3-L4 interspatium with bupivacaine hyperbaric 0.5% 15 mg and fentanyl 25 mcg as the adjuvant for subarachnoid block. Adductor canal block using ultrasound guide using 20 ml levo bupivacaine 0.25%. The outcome assessed using nurmmeric rating score (NRS), PONV, rescue analgetics, and ambulation score which includes: time up to go (TUG) with partial weight bearing, s-CST, 5xSST, 6 WMT straight leg raising (SLR) assessed at more than 48 hours.Discussion: PNB is proven to be reliable and effective for postoperative pain control, ambulation, rehabilitation and mobilization are also faster, adequate pain control will facilitate early mobilization and prevent side effects related to prolonged immobilization. Adductor canal block is a good modality as an adequate analgetic, the use of ACB can reduce use of rescue analgetic, reduce the incidence of PONV and support early mobilization.Conclusion: ACB in ACLR can facilitate adequate analgesia, does not require other rescue analgetics, reduce the incidence of PONV, and improve the ambulation as well as avoid other complications.